(untitled) (Journal of economic and management development research, 2026)
Against the background of the worsening global energy crisis and increasingly stringent ecological and environmental protection policies, the industrial cooling system, as a link with high energy consumption and high water consumption, has become a core issue of industrial sustainable development in terms of energy conservation, consumption reduction and green upgrading. Traditional cooling towers generally suffer from problems such as high energy consumption, low cooling efficiency, serious waste of water resources, and prominent noise and drift pollution, which are difficult to adapt to the current requirements of green and low-carbon development. This paper takes energy-saving and environmentally friendly cooling towers as the research object. By analyzing the policy background and market demand of the project implementation, it systematically demonstrates its technical feasibility, economic feasibility, environmental feasibility and social feasibility, identifies the potential risks of project implementation and puts forward countermeasures. The purpose is to provide a scientific basis for the research and development, application and large-scale promotion of energy-saving and environmentally friendly cooling towers, and promote industrial cooling systems to achieve the multiple goals of energy saving, water saving, environmental protection and efficient operation.